Adsorptive removal of organic dyes via porous materials for wastewater treatment in recent decades: A review on species, mechanisms and perspectives. (April 2022) - Lan, Dawei; Zhu, Huiwen; Zhang, Jianwen; Li, Shuai; Chen, Quhan; Wang, Chenxi; Wu, Tao; Xu, Mengxia
Abstract: Organic dyes, a type of high toxic and carcinogenic chemicals that present severe threats to human and aquatic life, are the most commonly seen organic pollutants in wastewater of industries such as textile, rubber, cosmetic industry etc. Various techniques for the removal of dyes are compared in this review. Adsorption has proven to be a facile and promising approach for the removal of dyes in wastewater. This work focuses on the latest development of various porous materials for the adsorption of organic dyes. The characteristics, functionalization and modification of different porous materials are also presented. Furthermore, adsorption behaviors and mechanism of these adsorbents in the adsorption of organic dyes are critically reviewed. Finally, challenges and opportunities for future research in the development of novel materials for the highly efficient removal of dyes are proposed. Graphical abstract: Image 1 Highlights: The review focuses on the development of various porous materials for the removal of dye adsorption. Illustrate the properties of different wastewater treatment for dyes removal. Summarize the unique features of different porous materials for dyes adsorption. Summarize the future direction for the development of porous materials for adsorption process.